Integrated Recycling and The Impact of Plastic Waste from Industry and Agriculture on The Environment - Anar Zhumadilova; Saule Zhigitova; Maira Turalina; Kuralay Aitekova (Qubahan Academic Journal)
The production, use, and waste generation of plastic products is steadily increasing worldwide, and therefore it is necessary to minimize their impact on the environment, as they are a considerable source of pollution and have a substantial impact on climate change. Plastic waste prevention and control is a vital component of China’s national strategy. The purpose of this study is to analyse various scenarios for predicting the impact of plastic waste from industry and agriculture on the environment in the period from 2019 to 2030. Three scenarios have been developed (the scenario of following the national policy of plastic waste management – NP, the scenario of increasing the recycling rate by 20% – RR, and the scenario of banning the incineration of plastic waste suitable for secondary use – IB). The analysis was carried out using a plastic waste management flow model, which calculates environmental indicators for each scenario. The main indicator used in the model was greenhouse gas emissions. It is established that due to the implementation of existing and proposed targets, greenhouse gas emissions will be reduced compared to the BAU scenario by 6.274 Mt CO2e for NP, by 11.523 Mt CO2e for RR and by 12.498 Mt CO2e for IB. A comparative analysis of scenarios with a discussion of their strengths and weaknesses was conducted, existing problems were considered and recommendations for possible solutions were provided. The preference for the RR scenario was reasoned. The results obtained can not only serve as an information source for scientific research, but also help practitioners solve the problem of plastic waste management in an environmentally safe and economical way.